Identification of a six‐miRNA panel in serum benefiting pancreatic cancer diagnosis. (21st April 2019) - Zou, Xuan; Wei, Jishu; Huang, Zebo; Zhou, Xin; Lu, Zipeng; Zhu, Wei; Miao, Yi
Abstract: Pancreatic cancer (PC) has posed a great health threat to a growing number of people all over the world. Detection of serum miRNAs, being sensitive, noninvasive, and easy to obtain, has a great potential of being a novel screening method for PC patients. In this study, we investigated miRNA expression levels in serum by qRT‐PCR. The study was divided into four phases: the screening, training, testing, and external validation stage. We firstly chose candidate miRNAs using Exiqon panels in the screening phase. Then, a total of 129 PC serum samples and 107 normal controls (NCs) were further analyzed in the following training and testing phases to identify differently expressed miRNAs. A cohort of 30 PC serum samples vs 30 NCs was used to confirm the diagnostic value of the identified miRNAs in the external validation phase. Moreover, miRNA expressions in additional 44 PC tumor tissue samples and the matched adjacent normal tissue samples as well as 32 pairs of serum‐derived exosomes samples were also further explored. As a result, we identified six significantly upregulated miRNAs in the serum of PC: let‐7b‐5p, miR‐192‐5p, miR‐19a‐3p, miR‐19b‐3p, miR‐223‐3p, and miR‐25‐3p. A six‐miRNA panel in serum was then established. The area under the receiver operating characteristic curves (AUC) for the panel was 0.910 for the combined training and testing phases, which showed higher diagnostic value than the individual miRNA. Prognostic value prediction using Cox's proportional hazards model and Kaplan‐Meier curves showed that increased serum miR‐19a‐3p was closely related to worse overall survival (OS). In addition, significant upregulation of miR‐192‐5p, miR‐19a‐3p, and miR‐19b‐3p was observed in both PC tissue and serum‐derived exosomes samples. In conclusion, we identified a six‐miRNA (let‐7b‐5p, miR‐192‐5p, miR‐19a‐3p, miR‐19b‐3p, miR‐223‐3p, and miR‐25‐3p) panel in the serum for PC early and noninvasive diagnosis. Abstract : We identified a six‐miRNA (let‐7b‐5p, miR‐192‐5p, miR‐19a‐3p, miR‐19b‐3p, miR‐223‐3p, and miR‐25‐3p) panel in the serum by multiple‐phase validation using qRT‐PCR for PC early and noninvasive diagnosis.